Low-temperature in situ CO2 enhanced oil recovery. (1st December 2022) - Wang, Shuoshi; Ogbonnaya, Onyekachi; Chen, Changlong; Yuan, Na; Shiau, Benjamin; Harwell, Jeffrey H.
Highlights: Urease catalyzed urea hydrolysis is effective in enhanced oil recovery applications. The pressure does not adversely affect the urease catalyzed urea hydrolysis up to 1500 psi. The newly developed system lowers the operating temperature of in situ CO2 enhanced oil recovery. Abstract: The new generation in situ CO2 enhanced oil recovery (ICE), which delivers CO2 by injection of a CO2 generating agent solution, was proven to offer robust recovery performances and potential cost and workflow benefits. However, the developed ICE systems are either formulated with a complex fluid recipe or a simplified version of a fluid system limited by high-temperature requirements. This work focused on removing the requirement of high reservoir temperature in our previous work while maintaining the simplicity of the single fluid injection system. Urease is studied as the catalyst for urea hydrolysis and evaluated experimentally. The denaturation behavior of urease and the reaction kinetics of the catalyzed urea hydrolysis process are tested at different urea concentrations, urease concentrations, and temperatures. Four sets of one-dimensional sand pack flowthrough experiments are conducted to verify the tertiary recovery potential of the newly developed low-temperature ICE system with different lithology. The extent of wettability alteration and the recovery mechanism for different lithologies was determined through core sample imbibition experiments and direct contact angle measurements. From the experimental results, urease-catalyzed urea hydrolysis is proven to be effective in tertiary oil recovery applications below the 50 °C reservoir temperature range with urea conversion ratio up to 68.7 %. The selected low-temperature ICE system (10 wt% urea solution with 31 U/g urease) had superior tertiary recoveries(Etr ) in the flowthrough test for sandstone(Etr  = 31.3 %) and carbonate(Etr  = 27.5 %) than the corresponding high-temperature cases. Imbibition tests of this improved formulation with various porous media show distinct wettability reversal trends towards a more water-wet state post imbibition. This trend is associated with the produced NH3 and CO2 due to urea hydrolysis. Both oil-aged sandstone and carbonate imbibition tests show noticeable water wetness improvement. The observations of this work significantly expand the operational envelopes of the current ICE system.